Growth accounting in the Republic of North Macedonia - Elizabeta Djambaska; Aleksandra Lozanoska (Institute of Economics – Skopje, 2019)
Growth accounting approach method is a useful technic which estimates the relative contribution of the factors of production to the economic growth rate and allow us to identify the current growth pattern. In this paper the focus is on the economic growth in the Republic of North Macedonia and the determination of the source of growth in the past two decades. The decomposition of the three basic factors labour, capital and productivity is calculated according to the Cobb-Douglas production function. The calculations are made for the whole 20 years period, first 1997 – 2017 and also for the group of five years period (1997-2001, 2001-2005, 2005-2009, 2009-2013 and 2013-2017). The results from the growth accounting in the Republic of North Macedonia shows that average growth rate in the past 20 years is 1.34%. Average growth rate of physical capital is 4.24% and of the labour is 1.28%. Contributions of physical capital to the growth rate in the Republic of North Macedonia is 1.40 percent points. Labour contribution is 0.86 percent points. The total factor productivity contributions to the average growth rate is negative -0.92 percentage points. The results of the calculations for the five years period confirm the low average rate of growth, and similar growth pattern of the average growth rate of capital and labour. The most concerning is the low and negative total factor productivity. This lead to the conclusions that economic growth in the Republic of North Macedonia is due to intensification of the labour. Hence, the growth is unsustainable in the long ran. Unsustainability of growth arise due to the low productivity of the production factors and the increased public debt which was made for financing the evidently low growth rate in the past. Recommendations are to focus on the investment in the physical capital, education, research and development, which will rise the quality of human capital and will increase total factor productivity.
Keywords: economic growth; employment; growth accounting; total factor productivity; Republic of North Macedonia